First aid kit management in selected tertiary institutions in Malaysia / Nurul Farhana Hamdan Fadel - Nurul Farhana , Hamdan Fadel (2018)
First aid kit provision in the workplace is a common practice by an employer to ensure safety, health and well-being of employees. Mismanagement of first aid items may end up producing a lot of scattered wastes all around the workplace that require the same attention as other healthcare wastes. Considering tertiary institutions as ‘mini cities’ of the workplace which involve a variety of activities, this study aims to ensure proper waste disposal and waste minimization practice of first aid items through holistic management approach. The main objective of this study is to identify the first aid kit management practice among tertiary institutions in Malaysia and to propose an effective first aid kit management system that can be adopted into any working environment. The method applied throughout this study was a random distribution of questionnaires to identify tertiary institutions to take part in this survey. Case studies were conducted in Taylor’s University Lakeside Campus and University of Malaya to understand the practice in more detail and also to validate the first aid management practice reflected through questionnaire results. The questionnaire data were then analyzed and compared to related regulations, guidelines and standards to identify the gap of current first aid kit management practice. From this study, the result demonstrated that the first aid kit management varies among institutions due to the different approaches of health and safety management system. Even though most of the institutions declare they practice waste minimization approach and proper waste disposal throughout first aid kit management, the effectiveness is still uncertain as per findings demonstrated through the case study. Issuance of first aid kit, replenishment control and waste disposal were found to be the main control elements in this study to ensure the effectiveness of first aid kit management in the workplace. Each of the proposed element can be adopted into any first aid kit management as waste minimization approach and to ensure proper waste disposal of the hazardous substances. This study demonstrated the possibility of managing small and scatter waste through effective and systematic management approach in order to protect adverse effect towards health and environment in the long term.